Sustainable Downscaled Catalytic Colorimetric Determination of Manganese in Freshwater Using Smartphone-Based Monitoring Oxidation of 3,3′,5,5′-Tetramethylbenzidine by Periodate - Sutasinee Apichai; Parichart Kummuntakoon; Thanawat Pattananandecha; Jakaphun Julsrigival; Kasirawat Sawangrat; Fumihiko Ogata; Naohito Kawasaki; Kate Grudpan; Chalermpong Saenjum (Molecules, 2022)
A sustainable downscaled procedure using smartphone-based colorimetric determination of manganese (Mn(II)) was developed. This novel Mn(II) determination procedure is proposed using a simple, available microwell-plate platform and a smartphone as a detector. This approach is based on the oxidation of 3,3′,5,5′-tetramethylbenzidine (TMB) by periodate using Mn(II) as a catalyst. The catalytic kinetics of Mn(II) under different conditions was investigated to determine the optimum condition where the different catalytic activities of various concentrations of Mn(II) evince. Under the optimum condition, the bluish-green product of oxidized TMB, proportioned to the concentration of Mn(II), was monitored using a smartphone camera, and the color signals were processed using ImageJ Software. The developed procedure showed great selectivity and sensitivity as linearity ranged from 1.8 × 10−6 to 4.6 × 10−5 M (0.1 to 2.5 μg/mL). The limits of detection and quantitation were 3.6 × 10−6 and 1.1 × 10−5 M (0.2 and 0.6 μg/mL), respectively. The determination of Mn(II) in freshwater samples was demonstrated to assess environmental water quality as an initial model to more easily promote water management according to the United Nations Sustainable Development Goals (UN-SDGs). The intensity of the red could be successfully applied to evaluate Mn(II) in canals and river water with no significant differences compared with the reference method of Inductively Coupled Plasma Optical Emission Spectrometry at a confidence level of 95%.